ANALISIS KESALAHAN SISWA SMP KELAS VIII DALAM MENYELESAIKAN MASALAH SOAL CERITA MATEMATIKA - Nurul Farida (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2015)
The aims of the research is to know mistakes and cause of mistakes mengetahui were done by students in in troubleshoot mathematics story problem. The research was a descrptive  qualitative. The subjects of the research was students of class VIII SMP Negeri 2 Karang Anyar. The result of the research are: 1) the mistakes made by students are: student incorrecting to change information that is given into mathematics expression, students can't determine formula, the students incorrectly concept, errors in interpreting the solution , do not make conclusions , errors in calculation;  2) cause students make mistakes  are : do not pay attention to a matter of intent , forget the formula , less familiar to a material , less given the questions varied, in a hurry, and less conscientious in performing the calculations